Application Of The Reflux Classifier Correlation To The Hydraulic Conveying Of Particles Up Steep Inclines - P. Stevenson (The Southern African Institute of Mining and Metallurgy, 2007)
Correlations for the critical velocity needed to hydraulically convey particles in horizontal, or near-horizontal, pipes are either explicitly dependent upon the shear stress imparted by the fluid upon the surface of the particle bed, or require a velocity and hydraulic diameter. Often such approaches are modified to account for pipe inclination by the introduction of simple factors. However, we assert that the physics that underpins the hydraulic conveying of particles in steep pipes (such as a directionally drilled oil well) is dissimilar to that which governs particle behaviour in horizontal pipes. In steeply inclined systems, a sliding sediment induces an upward counter flow and hence an autogenous contribution to the shear rate. The physics underpinning particle hydraulic conveying in steep systems is explored using the separation results of Laskovski et al.10